Ageing and memory medication: social rationales and consumption practices - Lopes, N.; Pegado, E.; Zózimo, J. R. (Sociology of Health and Illness, 2017)
This article focuses on the social rationales underlying the consumption or rejection of medication for memory by the elderly. Our analysis is set within the wider frame of the current use of psychopharmaceuticals for the enhancement of everyday performance, discussing its relationship to new cultures of ageing. Our results, from a recently concluded study, point to different patterns of investment in memory in old age. On the one hand, we found a willingness to consume medication for memory – a heterogeneous disposition split between the imaginary of disease and that of performance enhancement. On the other hand, we found a cultural resistance and scepticism towards the use of psychopharmaceuticals for performance purposes. This suggests that a new frame of psychopharmaceuticalization of old age – represented by memory medication – is prompting different rationales, ranging from consumption to resistance.